2022
DOI: 10.1002/acr.24991
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Social Disadvantage Associated with Childhood Arthritis: ACross‐SectionalAnalysis of the National Survey of Children's Health

Abstract: Objective Health disparities in juvenile idiopathic arthritis (JIA) remain poorly understood. Social disadvantage may have a cumulative impact on health, with recent analyses using combined scoring systems to measure their impact on outcomes. Our aim was to investigate cumulative social disadvantage on childhood arthritis by using a cumulative score to analyze its association with arthritis among a nationally representative sample of children. Methods A cross‐sectional analysis of the National Survey of Childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…For example, a recent study of children with childhood arthritis showed an association between cumulative social adversity and severity of disease, and is consistent with our data showing positive associations between cumulative social risk and inflammatory markers. 42 Our work also suggests that when biomarker results can inform clinical care, it may be helpful to collect samples from children at highest risk of having results at the extremes, such as those experiencing chronic and cumulative social adversity. Just as policies have been implemented to encourage screening for social adversity through reimbursements or requirements, as biomarkers become more clinically meaningful to informing care, policies incentivizing stress biomarker screening among those most at risk for extreme values could encourage clinical practice change.…”
Section: Discussionmentioning
confidence: 97%
“…For example, a recent study of children with childhood arthritis showed an association between cumulative social adversity and severity of disease, and is consistent with our data showing positive associations between cumulative social risk and inflammatory markers. 42 Our work also suggests that when biomarker results can inform clinical care, it may be helpful to collect samples from children at highest risk of having results at the extremes, such as those experiencing chronic and cumulative social adversity. Just as policies have been implemented to encourage screening for social adversity through reimbursements or requirements, as biomarkers become more clinically meaningful to informing care, policies incentivizing stress biomarker screening among those most at risk for extreme values could encourage clinical practice change.…”
Section: Discussionmentioning
confidence: 97%
“…Additional studies could assess correlation of accumulated social disadvantage (low guardian education, low household income level, underinsured status, and high adverse childhood experience score) with juvenile LS and SSc severity [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare disparities have been found to affect many health outcomes including disease severity, long-term outcome, and mortality [10][11][12]. Although access to care and diagnostic delay for several pediatric rheumatic diseases has been studied, there is limited information for juvenile LS and SSc [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Patients are often referred to several specialists before seeing a rheumatologist and obtaining a diagnosis. Healthcare disparities have been found to play an important role in access to care and diagnostic delay for several pediatric rheumatic diseases, but this issue has not been examined for juvenile LS and SSc (10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%